Sea level regulated tetrapod diversity dynamics through the Jurassic/Cretaceous interval - Jonathan P. Tennant (Nature Portfolio, 2016)
Reconstructing biodiversity trends in deep time is confounded by uneven sampling of the available fossil record. Here the authors apply a subsampling approach to a tetrapod fossil occurrence dataset and show extinction of important clades was driven by variation in sea level.